The inclusion process and Science education: a look at the structure and demand in municipal public schools in three municipalities in Rio Grande do Sul (Research, Society and Development, 2021)
Understanding the mechanisms that promote inclusion in science education is a necessary action for the democratization of school access and effective training within social diversity. The work sought to verify how the services aimed at the inclusion of students with disabilities and the promotion of science education occur. The research is characterized as exploratory and qualitative. The target audience were elementary schools in the municipal network, in three cities on the western border of Rio Grande do Sul. Data were obtained through information from municipal secretariats and questionnaires to managers. It was observed that in the evaluated municipalities, there is assistance and resources for the inclusion process, with frequent continuing education actions. However processes are more focused on general aspects of development and not for a particular area of ​​knowledge, and there are large gaps for an effective inclusion in science education.